2D → 3D interlocking Zn(II) arrays directed by uncoordinated groups: Fluorescent behaviors, recycling and enhancements of photocatalytic properties. (1st May 2018) - Liu, Guo-Cheng; Yu, Hui-Xuan; Liu, Xiang-Xiang; Wei, Meng-Yang; Lin, Jia-Feng; Wang, Xiang; Lin, Hong-Yan; Li, Xiao-Wu
Graphical abstract: Two 2D → 3D interlocking Zn(II) arrays based on "V"-type dipyridylamide and linear dicarboxylic ligands have been hydrothermally synthesized and the enhancements of photocatalytic properties by Ag and Fe 3+ were studied. Abstract: To investigate the effect of the uncoordinated groups of "V"-type dipyridylamide on the interlocking arrays of Zn(II) coordination polymers, [Zn(L 1 )(1, 4-bdc)]·H2 O (1 ) and [Zn(L 2 )(1, 4-bdc)]·H2 O (2 ) [L 1 = N, N ′-bis(pyridin-3-yl)-5-hydroxybenzene-1, 3-dicarboxamide, L 2 = N, N ′-bis(pyridine-3-yl)-5-methylbenzene-1, 3-dicarboxamide, 1, 4-H2 bdc = 1, 4-benzenedicarboxylic acid] have been hydrothermally synthesized and structurally characterized by IR, TG and X-ray single-crystal diffraction. Complex 1 is a 2D 6 3 network based on [Zn(1, 4-bdc)] zigzag chains and [Zn(L 1 )]2 loops, which is further extended into 2D → 3D parallel polycatenation array. Complex 2 features a 2D (4, 4) network derived from [Zn(1, 4-bdc)] zigzag chains and [Zn(L 1 )] helixes, which is further extended into 2D → 3D inclined interpenetration array. The effect of the uncoordinated groups of "V"-type dipyridylamide on the structures of the title complexes was discussed. The fluorescent behaviors of 1 –2 in aqueous solutions with Fe 3+, Co 2+, Ni 2+, Cu 2+, Zn 2+ were investigated. The photocatalytic properties of complexes 1 –2, Ag loaded CPs composite materials (Ag@1 –2 ) and Fe 3+ -functionalized composite materials (Fe 3+ @1 –2 ) for the degradation of methylene blue (MB) under ultraviolet light irradiation have been investigated.